ADVANCED MATERIALS-2007 : Proceedings of the 10th International Symposium on Advanced Materials, 03-07 September 2007, Islamabad, Pakistan - Farooque, M., editor 644251; Rizvi, Saiyid Athar Abbas, editor 240294; Ahmed Karim, editor 413453 (Islamabad, Pakistan : Secretariat International Symposium on Advanced Materials, 2007)
Esah Hamzah;